Specificity in the Susceptibilities of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus Clinical Isolates to Six Metal Antimicrobials - Natalie Gugala; Dennis Vu; Michael D. Parkins; Raymond J. Turner (MDPI AG, 2019)
In response to the occurrence of antibiotic resistance, there has been rapid developments in the field of metal-based antimicrobials. Although it is largely assumed that metals provide broad-spectrum microbial efficacy, studies have shown that this is not always the case. Therefore, in this study, we compared the susceptibilities of 93 clinical isolates belonging to the species Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus against six metals, namely aluminum, copper, gallium, nickel, silver and zinc. To provide qualitative comparative information, the resulting zones of growth inhibition were compared to the minimal inhibitory concentrations of three indicator strains E. coli ATCC 25922, P. aeruginosa ATCC 27853 and S. aureus ATCC 25923. Here, we demonstrate that the metal efficacies were species- and isolate-specific. Only several isolates were either resistant or sensitive to all of the six metals, with great variability found between isolates. However, the greatest degree of similarity was found with the E. coli isolates. In contrast, the susceptibilities of the remaining two collections, S. aureus and P. aeruginosa, were more highly dispersed. Using this information, we have shown that metals are not equal in their efficacies. Hence, their use should be tailored against a particular microorganism and care should be taken to ensure the use of the correct concentration.